Implementasi Sistem Informasi Keuangan Daerah, Kompetensi SDM, dan Pengawasan Internal terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Salehoddin, Salehoddin (Assyarikah: Journal of Islamic Economic Business, 2025)
This study falls within the domain of public sector accounting, emphasizing transparency and accountability in the management of local government finances. The objective of this research is to analyze the influence of the implementation of the Regional Financial Information System (SIKD), human resource (HR) competencies, and internal supervision on the quality of local government financial reports in East Java Province. A quantitative approach was employed using a survey method, with questionnaires distributed to 150 civil servants (ASN) working in the Regional Financial Management Agency (BPKD), the Regional Inspectorate, and financial staff in Regional Apparatus Organizations (OPD). The sample was determined purposively based on criteria such as direct involvement in financial management and reporting and at least one year of experience using SIKD. Data were analyzed using multiple linear regression, including validity and reliability testing, classical assumption tests, and significance testing through t-tests and F-tests. The results indicate that the implementation of SIKD, HR competencies, and internal supervision have a positive and significant effect on the quality of local government financial reports, both partially and simultaneously. These findings contribute significantly to the strengthening of local financial governance and provide a basis for policymakers to improve the quality of public financial reporting. The conclusion of this study highlights the importance of system integration, capacity building of human resources, and effective internal supervision as key determinants of accountable and transparent local government financial reporting.